Are clinical trial results transferable in the real life? - Natale, Enrico; Marsocci, Alfiera (Monaldi Archives for Chest Disease, 2016)
Generally in the clinical practice patients are more complex in comparison with those included in the clinical trials. In this article, we discuss three relevant items, which may implement the transferability of the clinical trial results in the real world. The observational studies have fewer restrictions on the number of patients included, due to more relaxed inclusion and exlusion criteria than in randomized clinical trials. The absence of randomization however may lead to potential for bias. The recurrent event analysis may extend the positive results of clinical trials regarding the reductions of the first primary endpoint event to total events, including those beyond the first event. This analysis is of great interest in the clinical practice, where recurrent events are common. Finally the reliability of subgroup analysis is discussed. Pre-specified subgroup analyses are more credible and valuable than post-hoc analyses. Riassunto Nella pratica clinica i pazienti sono generalmente più complessi rispetto alle popolazioni studiate nei trial clinici. Si rendono necessari pertanto strumenti di analisi che integrino i trial clinici. In questo articolo vengono esaminati alcuni punti di rilevante importanza nella definizione di una corretta applicabilità dei risultati dei trial clinici al mondo reale. Il primo punto riguarda il ruolo e i limiti degli studi osservazionali. Il secondo tratta delle analisi degli eventi ricorrenti, una modalità di analisi dei trial clinici che rende i risultati più aderenti alla vita reale, nella consapevolezza che limitare i dati di outcome al primo evento sia riduttivo rispetto alla necessità di stabilire che l’intervento studiato nel trial confermi la sua efficacia anche sugli eventi successivi al primo. Il terzo punto riguarda la controversa questione delle analisi per sottogruppi, uno strumento utile per generare ipotesi, ma discutibile quando impiegato per rimediare a trial con risultati negativi o estendere i risultati di trial positivi a sottopopolazioni particolari di pazienti.